Governance strategies in sustainable campus using Rasch model - Ngadiman, Norhayati; Abdul Rahman, Ismail; Kaamin, Masiri; Amiruddin, Mohd Hasril; Leman, Abdul Mutalib; Mokhtar, Mazlin (American Scientific Publishers, 2017)
In moving towards sustainability, university needs to establish a good governance strategy which practices to transform a positive sustainable culture toward successful green campus. Howe ver, due to constraint of knowledge and commitment regarding sustainability integration has caused weakness in the implementation of green concept in majority of Malaysian universities. This paper is presents one of the five dimensions of a developed hypot hetical integrated sustainable campus model which is university governance. The university governance dimension consists of 5 constructs and 23 items which are strategies for the university to be complied. These strategies were uncovered using questionnair e survey with 35 selected experts who are currently active in sustainable campus activities and researches. Collected data from this survey was analysed using Rasch method in Winstep software to measure items reliability, separation index, items polarity, item fit and item person map. Results from the analysis indicated that 19 strategies were significant to be implemented. Thus, it provides good information for universities to adopt these sustainable campus strategies in making their campus as a role mode l for a sustainable and conducive living environment.